151 Association between baseline factors and risk of injury amongst pre-professional dancers. (3rd March 2020) - Kenny, Sarah J; Vineetha Warriya, KV; Palacios-Derfingher, Luz; Whittaker, Jackie; Emery, Carolyn
Abstract : Background: Few investigations utilize evidence-informed pre-participation evaluation, inclusive injury definitions, and prospective surveillance to identify risk factors for dance-related injury. Objective: To identify baseline injury risk factors that may be associated with dance-related musculoskeletal (MSK) complaints in pre-professional dancers. Design: Prospective cohort study. Setting: Pre-professional ballet school; university dance program. Participants: Dancers registered in full-time ballet [n=85, 77 females, median (range) age 15 years (11–19)] and contemporary [n=60, 58 females, 19 years (17–30)] training. Assessment of risk factors: Pre-participation evaluation comprised of one-year injury history (yes/no), previous training (years), Athletic Coping Skills Inventory-28 (ACSI;score), body mass index (BMI;kg/m 2 ), total bone mineral density (g/cm 2 ), ankle plantar/dorsiflexion (degrees), active standing turnout (degrees), three lumbopelvic control tasks (high/low risk), unipedal dynamic balance (seconds), Y-Balance Test (cm). Weekly dance hours were self-reported throughout one academic year. Main outcome measurements: Self-reported MSK complaints (any physical complaint leading to difficulties participating in dance, regardless of consequences) were captured weekly by online modified Oslo Sports Trauma Research Centre's Questionnaire on Health Problems during academic year. MSK complaints were recorded (yes/no) for each participant for each week. Results: Response rate was 99%, with 81% (117/145) of dancers reporting at least one MSK complaint. Of the 1521 complaints (19% first-time, 81% recurrent), ankle (22%), knee (21%), and foot (12%) accounted for majority. Potential factors were identified through systematic review and a generalized linear mixed model was used to analyze the binary outcome measure. Injury history [Odds Ratio (OR) 7.37; 95% CI (3.41, 15.91)] and previous week's dance hours [OR 1.02; 95% CI (1.01, 1.03)] were significantly associated with MSK complaint. Conclusions: Prevalence of MSK complaints amongst pre-professional ballet and contemporary dancers is high and significantly associated with injury history and training volume. Future studies implementing injury prevention should incorporate training load monitoring to address the dynamic, recursive nature of dance injury etiology.